Fetal Reduction Could Improve but Not Completely Reverse the Pregnancy Outcomes of Multiple Pregnancies: Experience From a Single Center - Yimin, Zhu; Minyue, Tang; Yanling, Fu; Huanmiao, Yan; Saijun, Sun; Qingfang, Li; Xiaoling, Hu; Lanfeng, Xing (Frontiers in Endocrinology, 2022)
Objective: To investigate the effectiveness and limitations of multifetal pregnancy reduction (MFPR) on the improvement of pregnancy outcomes or triplet or twin pregnancies conceived by in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI). Methods: We performed a cohort study of women undergoing IVF or ICSI from 2002–2016 in reproductive center, women's hospital, Zhejiang University School of Medicine. The cohort included 502 women who underwent MFPR and 9641 non-reduced women. Pregnancy outcomes were gestational age (GA) at delivery, pregnancy loss, preterm delivery, low birth weight (LBW), very low birth weight (VLBW), and small for gestational age (SGA). Multiple linear regression and logistic regression models were used to compare pregnancy outcomes between groups. Results: Triplets reduced to singletons had a longer median GA (39.07 vs 37.00, P<0.001), and lower rates of LBW (8.9% vs 53.2%, P<0.001) and SGA (17.8% vs 44.7%, P=0.001) than those seen in triplets reduced to twins, with a similar pregnancy loss rate (6.7% vs 6.6%, P=0.701). Twins reduced to singletons had a comparable pregnancy loss rate (4.8% vs. 6.5%, P=0.40), a longer median GA (38.79 vs. 37.00, P<0.001), and lower rates of LBW (13.5% vs. 47.0%, P<0.001) and SGA (13.5% vs. 39.6%, P<0.001) than primary twins. Triplets reduced to twins had higher rates of LBW (53.2% vs. 47.0%, P=0.028 and SGA (44.7% vs. 39.6%, P=0.040) than primary twins, with a similar pregnancy loss rate (6.6% vs. 6.5%, P=0.877). Singletons reduced from triplets/twins had higher rates of preterm delivery (15.8% vs. 7.3%, P<0.001), LBW 12.3% vs. 4.32%, P<0.001), VLBW (2.3% vs. 0.4%, P=0.002), and SGA (14.6% vs.6.6%, P<0.001) than primary singletons, with a comparable pregnancy loss rate (5.3% vs. 5.4%, P=0.671). Conclusions: This study suggests that the pregnancy loss rate is similar between reduction and non-reduction groups. MFPR improves pregnancy outcomes, including the risk of preterm delivery, LBW, and SGA, but still could not completely reverse the adverse pregnancy outcomes of multiple pregnancies.